Interaction Model Parents-Adolescents in Adolescents are Risk Addiction of Drugs - Ah. Yusuf (Journal of Global Pharma Technology, 2019)
Background: One of problems in adolescents is risk of addiction to drugs that negative behavior disturbs the society. Adolescent had more spending time with friends in school and other places that have risk to addiction too Purpose: The aim of this study is analyzed interaction model of parents-adolescents in risk addiction of drugs based on King’s Goal Attainment theory. Method: This study was used cross-sectional design. 124 parents and adolescents from Senior High School through probability sampling that is simple random sampling. Questionnaire data were taken by parents’ (transactional factor, perception, judgment, and action), adolescents’ (transactional factor, perception, judgment, and actions), and parents-adolescents ’reaction, and parent-adolescents’ disclosure. Analysis method was used Partial Least Square (PLS). Results: Parents’ transactional factor influenced on parents’ perception (t=2,074), parents' perceptions influenced parent's judgment (t=2,697), parent’s judgment influenced parent’s action (t=2,396), parent’s action influenced parents-adolescents’ reaction (t=2.774), adolescents’ transactional factor not influenced adolescents’ perception (t=0,594), adolescents’ perception influenced adolescents’ judgment (t=5,744), adolescents’ judgment influenced adolescents’ action (t=2,118), adolescents’ action influenced parents-adolescents’ reaction (t=2.831), parents-adolescents’ reaction influenced parents’-adolecents’ interaction (t=3.048), parents’-adolescents’ interaction influenced parents’-adolescents’ disclosure (t=8,062). Conclusion: Many factors are being adolescent to risk addiction of drugs and can control with interaction models. Using interaction model of parents-adolescents so that practitioner can improve adolescent’s health promotion activities in community.Keywords: Adolescent, Parent, Risk addiction, Interaction.